Peran Koperasi Sekolah dalam Meningkatkan Keterampilan Kewirausahaan Siswa di SMK Negeri 1 Demak - Mustafidah Mustafidah; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to describe the role of school cooperatives in enhancing entrepreneurial skills among students at SMK Negeri 1 Demak. The study focuses on cooperative activities, student experiences, the role of teachers and supervisors, and the impact of student involvement on the development of entrepreneurial competencies. To address these issues, this research draws upon theories of entrepreneurship, cooperatives, and experiential learning. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed qualitatively using Miles and Huberman’s interactive model. The findings indicate that the school cooperative functions as an experiential learning platform that enables students to develop communication, teamwork, basic financial management, responsibility, and problem-solving skills through daily operational practice. The results also reveal that teachers and supervisors play an important role, although the integration between cooperative activities and entrepreneurship learning in the classroom remains limited. This study concludes that the school cooperative contributes significantly to the development of students’ entrepreneurial skills, but requires strengthened management, improved training, and institutional support to optimize its function as a business laboratory within the school environment